Variables ambientales y abundancia de los huevos de Anchoa mitchilli (Pisces: Engraulidae) en la laguna de Tamiahua, México - Díaz-Avalos, Carlos (2003)
Egg abundance of Anchoa mitchilli was studied in Laguna de Tamiahua, Veracruz during three annual cycles (84-85, 85-86 and 86-87). Our goal was to detect areas and seasons with high egg abundance and the possible association of such areas and seasons with covariates such as temperature, salinity, transparency, depth, location, season and year. The association was tested statistically using a Generalized Linear Model (GLM) with Gamma type error. The results suggest that not all the covariates considered have a significant effect on egg abundance (Student’s T, p>0.005). The significant effects show the presence of a seasonal component and that the effect of salinity on egg abundance is conditional to location. High average egg abundances for the three annual cycles were observed during summer. The presence of significant interactions (Student’s T, p<0.05) during the last two annual cycles shows that the variability of egg abundance is associated to surface temperature and salinity, conditionally to year.